Search for Excited Spin-3/2 Neutrinos at LHeC - A. Ozansoy; V. Arı; V. Çetinkaya (Advances in High Energy Physics)
We study the potential of the next ep collider, namely, LHeC, with two options s=1.3 TeV and s=1.98 TeV, to search for excited spin-1/2 and spin-3/2 neutrinos. We calculate the single production cross-section of excited spin-1/2 and spin-3/2 neutrinos according to their effective currents describing their interactions between gauge bosons and SM leptons. We choose the ν⋆→eW decay mode of excited neutrinos and W→jj decay mode of W-boson for the analysis. We put some kinematical cuts for the final state detectable particles and plot the invariant mass distributions for signal and the corresponding backgrounds. In order to obtain accessible limits for excited neutrino couplings, we show the f-f′ and ciV-ciA contour plots for excited spin-1/2 and excited spin-3/2 neutrinos, respectively.